Comprehensive Safety Exposure‐Response Analysis to Support Ritlecitinib Dose Selection - Yeamin Huh; Ruolun Qiu; John Prybylski; Jessica Wojciechowski; Yuchen Wang; Vivek S. Purohit (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Ritlecitinib is a kinase inhibitor drug recently approved for the treatment of alopecia areata (AA) in both adults and adolescents based on a single, combined Phase 2b/3 study. Various QD doses with and without a loading dose have been evaluated in the pivotal Phase 2b/3 study. Therefore, characterization of the ritlecitinib safety profile becomes important to help inform the dose selection within the single Phase 2b/3 trial in conjunction with efficacy analysis. The purpose of this study is to characterize the safety profile of ritlecitinib with comprehensive exposure‐response (ER) analyses. The concentration‐QTc model was developed using a scientific white paper model, indicating no evidence of ritlecitinib‐induced QTc prolongation. The semi‐mechanistic PK/PD model well described the longitudinal profile of lymphocytes, indicating ritlecitinib‐induced decrease in lymphocytes was marginal and the incidence of Grade 3/4 lymphopenia was predicted to be small across the investigated dose range except for a slight increase in the loading dose regimen. The ritlecitinib‐dependent increase in the incidence of infections and rash was successfully described by a Poisson regression model using time‐weighted average concentration as an exposure metric, indicating that the dose‐dependent increase in the incidence of AEs is not dose‐proportionally large in the investigated dose range. Covariate analysis within each model indicated that the safety ER relationship of ritlecitinib is similar across all the patient subgroups and no unique safety risks associated with ritlecitinib are anticipated in adolescent patients. Therefore, this comprehensive safety ER analysis supported the selection of the ritlecitinib 50 mg non‐loading dose regimen for AA patients including both adults and adolescents.